ANALISIS KEBUTUHAN SUMBER DAYA INSANI PERBANKAN SYARIAH INDONESIA BERBASIS KOMPETENSI - RATNA KUSUMADEWI; SAMSUBAR SALEH; RIFQI MUHAMMAD (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2022)
Indonesia is one of the countries that is quite consistent in developing the Islamic financial industry, and it can be seen from the development of Islamic financial institutions (IFIs). However, one of the main problems currently faced by the Indonesian Islamic finance industry is the lack of human resources who have competency and qualifications according to the profile of Islamic banks. This paper aims to analyze the organizational structure of Islamic banking to map the need of human resource in accordance with their competencies. The analysis results of this paper are expected to contribute to the development of human resources in accordance with the needs of Islamic banks.